Exploring the Mechanism for the Photocatalytic Degradation of Oxytetracycline in Water using TiO2 and Supplementary Oxidants - Thao, Tran Quoc; Thu Hien, Ngo Thi; Lam , Phan Thanh; Huy, Nguyen Nhat; Thi, Pham Tan; Thanh, Nguyen Trung; Toan, Phan Phuoc; Thich, Le Tri; Thuy, Nguyen Thi (Applied Science and Engineering Progress, 2025)
The persistent presence of antibiotics in wastewater, exemplified by oxytetracycline (OTC), poses environmental risks, necessitating robust removal strategies. This study investigates the effectiveness of photocatalysis utilizing TiO2 (P25) treated at various temperatures, combined with different oxidants such as hydrogen peroxide (H2O2), potassium peroxydisulfate (PDS), potassium peroxomonosulfate (PMS) under diverse experimental conditions. The research systematically explores the impact of temperature, pH, and oxidant concentration on the efficiency of OTC degradation. Our findings reveal that the combination of P25/500, PDS, UV irradiation, and stirring demonstrates superior OTC degradation, surpassing 99% efficiency after 180 min. Optimal pH conditions are identified, emphasizing the importance of balancing acidity for enhanced performance. The study also provides insights into the optimal PDS concentration, indicating a threshold beyond which further increases yield diminishing returns. Mechanistic understanding is enhanced through scavenger experiments, elucidating the pivotal role of reactive oxygen species, particularly O2•−, in the photocatalytic process. This research offers a practical framework for TiO2-based photocatalysis in wastewater treatment, emphasizing tailored conditions for efficient antibiotic removal. The outcomes contribute valuable insights to the development of sustainable wastewater treatment protocols targeting antibiotic pollutants.